Factors affecting the intention of COVID-19 vaccination in Korean patients with myasthenia gravis: A survey-based study - Kim, Sooyoung; Jeong, Seong Ho; Shin, Ha Young; Kim, Seung Woo (Frontiers in Neurology, 2022)
Objective: To investigate the intention of coronavirus disease 2019 (COVID-19) vaccination in Korean patients with myasthenia gravis (MG) and to determine the factors that influence their attitude towards COVID-19 vaccination. Materials and Methods: We conducted a questionnaire survey of 160 Korean patients with MG. The questionnaire consisted of five categories, including vaccination status, willingness to get vaccinated, general concerns over vaccination, impact of MG diagnosis on vaccination decision, and MG-specific concerns over vaccination. The responses were rated from 1 (no intention or influence) to 5 (significant intention or influence). We compared the clinical factors between patients willing to get vaccinated (willing group) and those who were neutral or unwilling (hesitant group). Results: The average score of willingness to get vaccinated was 4.1±1.2 (Likert score, 1-5). The hesitant group demonstrated higher proportions of women, patients with MG Foundation of America (MGFA) classification ≥III at nadir, and those who had experienced myasthenic crisis than the willing group (women, p=0.027; MGFA classification≥III, p=0.018; myasthenic crisis, p=0.027). Scores for the willingness to get vaccinated (Likert score, 1-5) were negatively correlated with the MGFA classification at nadir (r=-0.235, p=0.003), degree of general concern about vaccination (r=-0.362, p<0.001), and impact of MG diagnosis on vaccination decision (r=-0.365, p<0.001). In the path analysis, the MGFA classification at nadir was negatively associated with the willingness to get vaccinated by increasing the impact of MG diagnosis on vaccination decision. Conclusion: MG diagnosis, maximum disease severity, and general concerns about vaccination influenced the intention to get vaccinated.